PHENOMENOLOGY OF MANAWI IN SUNDANESE INFORMAL CREDIT PRACTICES - Ilham Nurjaman (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2026)
While existing literature extensively examines the socio-economic mechanisms of informal credit, the subtle linguistic strategies that mediate these vulnerable transactions remain underexplored. This study investigates the semantic shift of the Sundanese term manawi within the framework of social embeddedness and informal credit practices in Bandung. The primary objective is to analyze how this linguistic transformation functions as a social negotiation tool in relationship-based economic transactions. Employing a qualitative descriptive-interpretative phenomenological method, data were gathered through semi-structured, in-depth interviews with five purposive Sundanese-speaking participants and analyzed via Moustakas's framework. The results reveal that manawi has expanded from its conventional role as a modal adverb meaning